2008
DOI: 10.1177/112972980800900208
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Access Questionnaire: Assessing Patient-Reported Views of Vascular Access

Abstract: Patients appear to be primarily concerned with the appearance of their access and cannulation-related complications, particularly the elderly. Better education about the risk of adverse events with catheters and the implementation of measures aimed at reducing cannulation-related complications may help to increase fistula rates and improve patient satisfaction with their vascular access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 27 publications
5
92
0
Order By: Relevance
“…A minority of patients (12% to 22%) dialyzing through an AVF were at least moderately bothered by pain, bleeding, bruising, and/or appearance. Older patients were more likely to report more symptoms with catheters than younger patients (22). As many as 9% of patients offered an AVF consistently refused surgery, and hesitancy to undergo access surgery in the face of failed prior accesses also deters patients from having a fistula created or revised (23).…”
Section: Are Patient Choices Contributing To Tcc Use?mentioning
confidence: 99%
“…A minority of patients (12% to 22%) dialyzing through an AVF were at least moderately bothered by pain, bleeding, bruising, and/or appearance. Older patients were more likely to report more symptoms with catheters than younger patients (22). As many as 9% of patients offered an AVF consistently refused surgery, and hesitancy to undergo access surgery in the face of failed prior accesses also deters patients from having a fistula created or revised (23).…”
Section: Are Patient Choices Contributing To Tcc Use?mentioning
confidence: 99%
“…7 The results of a study conducted in 2008 showed that hemodialysis patients collectively suffer from needle pain, which is one of the factors causing patients over 65 years to give up hemodialysis. 8 McCaffery argues that pain is whatever the person experiencing it describes it to be and exists whenever the person experiencing it says that it does. 9 The perception of pain includes different mental processes, such as the individual's feelings and beliefs about pain.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, pain and compressive symptoms can decrease quality of life in these patients. 2,6 There are several proposed etiologies of aneurysmal degeneration of AVF, including repeated cannulation of a particular segment of vein and venous hypertension due to central vein stenosis. It is also proposed that some veins are of weaker tissue quality, and thus, can explain those aneurysmal changes in patients before dialysis access.…”
Section: Discussionmentioning
confidence: 99%